Morphological and molecular evidence supporting advantages of apomictic seed production in castor bean (Ricinus communis L.) - Maedeh Setayeshnasab; Mohammad R. Sabzalian; Mehdi Rahimmalek; Tahmineh Lohrasebi (BMC Plant Biology)
Abstract Background Ricinus communis L. is a large plant from the spurge family (Euphorbiaceae), grown for industrial and medicinal purposes. In this research, progenies obtained from three types of reproduction, including apomixis, self-pollination, and open-pollination from a worldwide collection of castor bean (14 genotypes), were evaluated based on yield components and agro-morphological traits and the amount of inbreeding depression and apomixis advantages were estimated in each genotype using offspring. In addition, the expression of eight candidate genes for apomixis (including Helic, SERK, BBM, LEC1, ABI3, FUS3, WUS, and GLC) was assessed during three stages of floret development in both apomixis and open-pollination reproductions. Results Results of data analysis demonstrated that inbreeding depression for most traits in self-pollinated progenies than apomictic progenies (IDA) was higher compared to inbreeding depression than open-pollinated progenies (IDO). Additionally, the highest inbreeding depression was for seed yield per plant, and genotypes of Isfahan and Benin had the highest IDA (-53.78%) and IDO (-76.95%) for seed yield per plant, respectively. In contrast, apomixis advantage was positive for most traits, and apomixis advantage relative to self-pollinated progenies (AAS) was higher than apomixis advantage relative to open-pollinated progenies (AAO). The highest apomixis advantage was for seed yield per plant, and the highest AAO (424.51%) and AAS (333.85%) for this trait were observed in the Benin genotype. The expression levels of apomixis candidate genes increased in apomixis reproduction vs. open-pollination one and the greatest expression difference was observed for Helic and ABI3 genes promoting somatic embryogenesis in earlier stages of seed development. Conclusions According to the results of this study, apomixis is probably advantageous over both self-pollination and open-pollination methods of reproduction in castor bean and the apomictic progenies were superior in most traits, which is probably due to the accumulation of undesirable alleles in the self-pollinated progenies (inbreeding effects) and the segregation of desirable characteristics in the open-pollinated progenies (segregation effect).